Bread cofortified with folic acid and vitamin B-12 improves the folate and vitamin B-12 status of healthy older people: a randomized controlled trial. - Winkels, R; Brouwer, I; Clarke, R; Katan, M; Verhoef, P (2008)
BACKGROUND: Mandatory fortification of flour with folic acid has reduced the number of neural tube defects in North America. Concerns that high intakes of folic acid might mask vitamin B-12 deficiency in older persons have delayed the introduction of fortification in many European countries. Cofortification of flour with folic acid and vitamin B-12 could simultaneously improve folate and vitamin B-12 status. OBJECTIVE: The objective was to estimate the effect of the consumption of bread fortified with modest amounts of folic acid and vitamin B-12 on folate and vitamin B-12 status in healthy older persons living in the Netherlands, where folic acid fortification is not taking place. DESIGN: Men and women aged 50-75 y were randomly assigned in this 12-wk double-blind, placebo-controlled trial to consume bread fortified with 138 mug folic acid and 9.6 mug vitamin B-12 daily (n = 72) or unfortified bread (n = 70). RESULTS: The consumption of fortified bread increased serum folate concentrations by 45% (mean: 6.3 nmol/L; 95% CI: 4.5, 8.1 nmol/L) and serum vitamin B-12 concentrations by 49% (mean: 102 pmol/L; 95% CI: 82, 122 pmol/L) relative to the placebo group. Fortified bread increased erythrocyte folate concentrations by 22% and holotranscobalamin concentrations by 35%; it decreased homocysteine concentrations by 13% and methylmalonic acid concentrations by 10%. Consumption of fortified bread decreased the proportion of individuals with marginal serum vitamin B-12 concentrations (<133 pmol/L) from 8% at enrollment to 0% after 12 wk. CONCLUSION: Bread fortified with modest amounts of folic acid and vitamin B-12 will improve folate and vitamin B-12 status and a considerable proportion of vitamin B-12 deficiency in older people. This trial was registered at clinicaltrials.gov as NCT00353353.